A histomorphometric study on treated and untreated ceramic filled PEEK implants versus titanium implants: Preclinical in vivo study. Issue 3 (19th December 2019) - El Awadly, Tarek A.; Wu, Gang; Ayad, Mohamed; Radi, Iman A. W.; Wismeijer, Daniel; Abo El Fetouh, Hamdy; Osman, Reham B.
Abstract: Objectives: To investigate the osseo‐integrative behavior of untreated (UCFP) and sandblasted ceramic filled PEEK (SCFP) implants in comparison with titanium implants through measurement of bone implant contact (BIC) and bone density (BD). Materials and methods: Nine implants from each type were inserted into 9 dogs in which every experimental dog received the three different implants in the lower border of the mandible. The animals were euthanized after 3 months and extracting bone blocks containing implants followed by blocks preparation for histological examinations. Results: BIC and BD were significantly higher in titanium and SCFP compared with UCFP group ( p = .007) and ( p = .012), respectively. Aluminum blasting increased the bone ingrowth and bone implant contact when compared to machined surfaces of untreated PEEK implants. Conclusion: In conclusion, sandblasting with 110 µm aluminum oxide particles can be proposed as a suitable surface treatment that enhances hydrophilicity of CFP. Further in vivo animal studies are still needed to confirm the findings of this study.